Common Questions When Using Soil Moisture Sensors for Citrus and Other Fruit Trees - Eric Herrera; Sandra M. Guzmán; Eduart Murcia (EDIS)
This guide is for Extension personnel who may encounter questions from growers about the functioning and accuracy of soil moisture sensors (SMSs) for fruit tree production. The 4-page publication focuses on two types of handheld sensors currently used in Florida for irrigation management of citrus and other trees: the transmission line oscillator (TLO) and time-domain transmissometer (TDT). Written by Eric Herrera, Sandra M. Guzmán, and Eduart Murcia, and published by the UF/IFAS Department of Agricultural and Biological Engineering, February 2021.